(untitled) (ItalianoLinguadue, 2024)
Questo studio analizza le politiche linguistiche familiari (FLP) e le pratiche linguistiche delle famiglie italo-lituane a Vilnius, Lituania, esaminando l’interazione tra fattori interni ed esterni. Attraverso interviste qualitative semi-strutturate condotte con cinque famiglie, i dati sono stati analizzati seguendo il modello teorico di X. Curdt-Christiansen. La FLP è influenzata da fattori esterni socioeconomici, sociopolitici, socioculturali, sociolinguistici e interni emotivi, identitari, culturali, agency dei bambini e convinzioni sull’impatto genitoriale. Lo studio mira a esplorare i comportamenti linguistici familiari, le variazioni nei fattori interni ed esterni che influenzano le FLP, le tendenze prevalenti in questo gruppo demografico e i fattori più influenti. I risultati rivelano una maggiore variabilità nei fattori interni legati ai valori e alle convinzioni dei genitori rispetto a quelli esterni, modellati dall’ambiente sociale della famiglia. Fattori emotivi e socioeconomici, insieme alle convinzioni sull’impatto genitoriale, emergono come i più influenti. Forti convinzioni e opinioni linguistiche dei genitori sono associate a una FLP più chiara e a un migliore sostegno allo sviluppo bilingue dei figli, indipendentemente dalla strategia linguistica adottata. Family language policy: a study of Italo-Lithuanian families in Lithuania This study investigates family language policy (FLP) and linguistic practices of Italo-Lithuanian families in Lithuania. FLP is explicit and/or implicit language planning for language use in the home and among family members which is determined by independent yet interconnected internal and external factors. The data consists of 5 qualitative semi-structured interviews conducted with Italo-Lithuanian families residing in Vilnius. This data then was analysed following the theoretic model of X. Curdt-Christiansen, according to which FLP is influenced by external socio-economic, socio-political, socio-cultural, socio-linguistic factors and internal emotional, identity, cultural factors, child agency and parental impact belief factors. The aim of the study is to analyse the families’ linguistic behaviour, the variations within the internal and external factors that influence the FLP, observe the tendencies of the FLP that occur within this demographic, and recognise the most influential factors. The study shows a greater variation within the internal factors that are based on the parents’ values and beliefs, compared to a much lesser variability within the external factors that depend on the families’ social environment. The FLP was influenced the most by emotional and socio-economic factors as well as parental impact beliefs. Parents that held strong convictions and linguistic opinions had more defined (even if implicit) FLP and were more successful in supporting their children’s bilingual development regardless of the linguistic strategy used